EFFECT OF CERTAIN CHROMOSOME REGIONS OF TRITICUM TIMOPHEEVII ON THE FORMATION OF PEST RESISTANCE AND QUANTITATIVE TRAITS IN COMMON WHEAT - E. M. Timonova; I. N. Leonova; I. A. Belan; L. P. Rosseeva; E. A. Salina (Вавиловский журнал генетики и селекции, 2014)
The effects of introgression fragments from Triticum timopheevii Zhuk. (2n = 28, AtAtGG) and their combinations on resistance to leaf rust, stem rust, powdery mildew, and some quantitative traits were assessed in 15 common wheat introgression lines. Molecular and cytological analyses of the lines demonstrated an advantage of combined use of various marker types in comprehensive characterization of hybrids and detection of translocations and substitutions. Resistance tests to various fungal diseases showed that the lines containing introgression fragments of chromosome 5G were completely resistant to the West Siberian populations of leaf rust and to the stem rust population of the Omsk region. Lines 3862-5 and 3862-15, containing a fragment of the long arm of chromosome 2G, were resistant to West Siberian stem rust populations. No negative effects of the alien genetic material on yield and other quantitative traits were noted. In addition, positive effect of the 2G chromosome fragments of Triticum timopheevii on ear grain number was established. Thus, the introgression lines can be used in breeding programs as donors of resistance genes to fungal diseases.